Building Customer Loyalty through Trust and Satisfaction: The Role of Service Quality and Product Value in the Digital Banking Era - Wahyudin Yahya; Andi Mappatompo; Muchriana Muchran (Scieclouds Publishing, 2026)
This study aims to analyze the influence of e-service quality and product value on e-trust and e-satisfaction, and their effect on the e-loyalty of BRImo application users, both directly and through e-trust and e-satisfaction as mediating variables. A quantitative survey approach was used, involving 180 BRImo customers aged 18-35 years at the BRI Bantaeng Lamalaka Unit branch office. Data were analyzed using Structural Equation Modeling (SEM) with AMOS. The results show that e-service quality and product value have a positive and significant effect on e-trust and e-satisfaction, but no significant direct effect on e-loyalty. E-trust and e-satisfaction have a positive and significant effect on e-loyalty, and both act as significant mediators in the relationship between e-service quality and product value on e-loyalty. These findings confirm that customer loyalty in digital banking is built through indirect mechanisms, making the strengthening of trust and satisfaction a key strategy for improving BRImo customer loyalty.